2020
DOI: 10.1002/tox.22939
|View full text |Cite
|
Sign up to set email alerts
|

l‐Carnitine protects against 1,4‐benzoquinone‐induced apoptosis and DNA damage by suppressing oxidative stress and promoting fatty acid oxidation in K562 cells

Abstract: Widespread occupational and environmental exposure to benzene is unavoidable and poses a public health threat. Studies of potential interventions to prevent or relieve benzene toxicity are, thus, essential. Research has shown l‐carnitine (LC) has beneficial effects against various pathological processes and diseases. LC possesses antioxidant activities and participates in fatty acid oxidation (FAO). In this study, we investigated whether 1,4‐benzoquinone (1,4‐BQ) affects LC levels and the FAO pathway, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…To identify the metabolites that caused the differences in antitumor activity between the WT and AalaeA OE29 extracts, the antitumor compounds involved in KEGG pathways were first screened, including lanosterol [24], ergosterol [25], myricetin [26], epicatechin gallate [27], geraniol [28], humulene [29], (2E,6E)‐farnesol [30], AICAR [31], trans‐cinnamic acid [32], cinnamaldehyde [33], carnitine [34], and l ‐methionine [35].…”
Section: Resultsmentioning
confidence: 99%
“…To identify the metabolites that caused the differences in antitumor activity between the WT and AalaeA OE29 extracts, the antitumor compounds involved in KEGG pathways were first screened, including lanosterol [24], ergosterol [25], myricetin [26], epicatechin gallate [27], geraniol [28], humulene [29], (2E,6E)‐farnesol [30], AICAR [31], trans‐cinnamic acid [32], cinnamaldehyde [33], carnitine [34], and l ‐methionine [35].…”
Section: Resultsmentioning
confidence: 99%
“…These findings indicated that benzene induces mitochondrial dysfunction and oxidative stress, which may be one of the causative mechanisms of hematotoxicity [ 67 , 90 ]. In a recent study, Sun, Man, et al, (2020) [ 93 ] demonstrated that co-treatment with L-carnitine in K562 erythroleukemia cells treated with 1,4-benzoquinone, reduces the rate of apoptosis, DNA damage, reduces oxidative stress and promotes the β-oxidation of fatty acids.…”
Section: Resultsmentioning
confidence: 99%